Online learning in cultural studies in post-pandemic era: a case of international students’ experience in Universiti Teknologi Malaysia - Mohd Fakhruddin, Faizah; Mohd Noor, Noor Azlan; Mahfar, Mastura; Mohd Fakhruddin, Fathiyah; Abd.Hamid, Mohd Azhar; Abdul Rahman, Rabeatul Husna; Rusbadrol, Noraini (Human Resource Management Academic Research Society, 2023)
This article addresses several issues relating to international students’ experiential learning via online learning application in cultural studies at Universiti Teknologi Malaysia (UTM) during the post-pandemic era. The main objective of this study is to analyse the challenges encountered by international students in the ‘Malaysian Society and Culture’ course, a UTM preparatory course offered for newly registered post-graduate international students. The course was designed to expose new UTM post-graduate students, particularly international students to the uniqueness of the Malaysian multi-ethnic, multi-religious, and multi-cultural society. This study employed a qualitative method using written semi-structured open-ended interviews in the e-learning platform. In relation to this, 15 international students who registered for the course in semester 1, 2021/2022 academic session and semester 2, 2021/2022 session were selected using purposive sampling method. Thematic analysis was employed in analysing the data. The findings of this study had shown that the challenges observed included the absence of direct experiential learning, internet accessibility, time zone difference, adjustment problem, and accessibility to online resources. The results also provided valuable insights in relation to the application of online learning in the context of cultural studies. This is pertinent as far as the educational and sociological body of knowledge is concerned.